Short Report: Patterns of Organ Involvement in Recurrent Melioidosis - Limmathurotsakul, D; Chaowagul, W; Day, N; Peacock, S (2009)
Recurrent melioidosis can be caused by two different mechanisms: relapse or re-infection. We examined the pattern of organ involvement in the first and second episodes in individual patients. Evaluation of 140 patients with recurrence showed that similar patterns of disease occurred during the first and second episode, independent of whether this was caused by relapse or re-infection. Copyright © 2009 by The American Society of Tropical Medicine and Hygiene.